Heroes of the environment : true stories of people who help protect our planet - Rohmer, Harriet; McLaughlin, Julie (San Francisco : Chronicle Books, 2009)
This inspiring book presents the true stories of 12 people from across North America who have done great things for the environment. Heroes include a teenage girl who figured out how to remove an industrial pollutant from the Ohio River, a Mexican superstar wrestler who works to protect turtles and whales, and a teenage boy from Rhode Island who helped his community and his state develop effective e-waste recycling programs. Plenty of photographs and illustrations bring each compelling story vividly to life.
Keywords: Environmentalists -- Biography